Movie Recommender System Using Genetic AlgorithmPaper (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A movie recommendation is important in our social life due to its strength in providing spectacularly improvised entertainment. Such a system can suggest a set of movies to users based on their interest of the movies. A set of movie recommendation systems have been proposed In this project we have explored and implemented various movie recommendation systems that have the ability to recommend movies to a new user as well as the others. It mines movie databases to collect all the important information, such as, popularity and attractiveness, required for recommendation. It generates movie swarms not only convenient for movie producer to plan a new movie but also useful for movie recommendation. The implemented systems prove effectiveness of the proposed systems